Comparison between AMS 700™ CX and Coloplast™ Titan Inflatable Penile Prosthesis for Peyronie's Disease Treatment and Remodeling: Clinical Outcomes and Patient Satisfaction. (4th December 2012) - Chung, Eric; Solomon, Matthew; DeYoung, Ling; Brock, Gerald B.
ABSTRACT: Introduction.  The implantation of inflatable penile prosthesis (IPP) with simultaneous manual penile remodeling allows for men to undergo a single procedure aimed at correcting both the penile deformity/curvature and erectile dysfunction (ED). Aim.  To evaluate the clinical outcomes and patient satisfaction in men with Peyronie's disease (PD) and ED who underwent AMS 700™ CX and the newer Coloplast™ Titan inflatable penile prosthesis (IPP) implant. Main Outcome Measures.  Patient demographics, type of IPP, clinical outcomes, post‐implant sexual characteristics, and overall patient satisfaction. Methods.  A single‐center retrospective review of clinical database and prospective telephone survey were conducted in all men with PD who underwent IPP between January 2006 and November 2010. Results.  A total of 138 patients with an average age of 57.7 (32 to 80) underwent AMS 700 CX (88 patients) and Coloplast Titans (50 patients) IPP implantation during the 5‐year period. The majority of patients (91%) had only one IPP implantation. The IPP clinical outcomes include eight (6%) revision surgery for device malfunction and three (2%) device explantation for prosthesis infection. While there was no statistically significance in device survival between the two devices, the trend favored AMS 700 CX over Titan (5‐year Kaplan‐Meier estimates of mechanical survival were 91% vs. 87%, P  > 0.05) and both IPPs provided similar penile straightening without the need for revision surgery. Most men (79%) reported great satisfaction following CX or Titan implants with greater than two thirds of men reported greater self‐confidence and 82% of patients would undergo the same operation again. Conclusions.  AMS 700™ CX and Coloplast™ Titan IPP implantation and penile remodeling appeared to provide permanent penile straightening and high patient satisfaction without an increase risk of revision surgery.Chung E, Solomon M, DeYoung L, and Brock GB. Comparison between AMS 700™ CX and Coloplast™ Titan inflatable penile prosthesis for Peyronie's disease treatment and remodeling: Clinical outcomes and patient satisfaction. J Sex Med 2013;10:2855–2860.